PENGEMBANGAN APLIKASI BERBASIS ANDROID PADA MATA PELAJARAN IPS MATERI KENAMPAKAN ALAM DAN KERAGAMAN SOSIAL BUDAYA KELAS V SD NEGERI 3 GETAS TEMANGGUNG - Novitasari, Novitasari; Jayanti, Atik Kurnia; Zulfiati , Heri Maria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Research on Android-based application development in social studies subjects. The lack of use of technology-based learning media in elementary schools makes teaching and learning activities monotonous. This causes learning objectives not to be achieved well and students are less motivated in learning. This research aims to develop Android-based application learning media, as well as determine the feasibility of Android-based application learning media regarding Natural Appearance and Socio-Cultural Diversity. The sample in this research was 19 class V students at SD Negeri 3 Getas Temanggung. This type of research is RnD with the ADDIE research method which consists of five stages, namely Analyze, Design, Development, Implementation and Evaluation. The data collection techniques used were observation, interviews and questionnaires. At the end of this research, a product was produced in the form of an Android-based learning media application for fifth grade elementary school students. The overall results of the feasibility test and user test of Android-based applications involving media experts, material experts, language experts, class V teachers and class V students are in the very good category. It can be concluded that the suitability of the media is very good in social studies learning in elementary schools. This application can be used to help teachers in the social studies learning process, and can increase students' interest in learning.